Gravitational Potential Energy in Iberia: A Driver of Active Deformation in High‐Topography Regions. Issue 11 (29th November 2018) - Neres, M.; Neves, M. C.; Custódio, S.; Palano, M.; Fernandes, R.; Matias, L.; Carafa, M.; Terrinha, P.
Abstract: In this study, we present a new estimation of the gravitational potential energy (GPE) in Iberia and use numerical modeling to evaluate its relative contribution to the present‐day stress field and deformation. We also present an improved (larger time span and denser coverage) compilation of Global Navigation Satellite System velocities, which we use to compute the strain rate field of Iberia. We take advantage of recent neotectonic modeling developed for Iberia and northwest Africa to study the isolated dynamic contribution of GPE‐related stresses. We present two models—one including only the stress generated by GPE and another reproducing the net stress field—and compare their predictions with the most up‐to‐date compilations of stress indicators, hypocenter clusters, and geodetic strain rates. The main effect of GPE is to induce second‐order spatial variations in the stress field. GPE appears to play an important role in high‐topography regions, where it explains deviatoric stress patterns mainly associated with extensional regimes. In north Iberia, especially in the Pyrenees and Cantabria, GPE causes an extensional regime over the highest peaks. In the Iberian Chain and eastern Betics, GPE is in agreement with the observed extensional deformation. Normal focal mechanisms of shallow earthquake clusters appear to be related with GPE maxima and GPE‐induced extensional regimes. Wavelength analysis suggests that both GPE and the long‐wavelength topography of intraplate Iberia record the plate boundary forces that acted in Iberia during the Alpine orogeny at Eocene to lower Miocene times. Key Points: We present a new estimation of GPE in Iberia, which is compared to stress indicators and to a new/updated Iberian strain rate field GPE leads to local deviations in the main tectonic stress field in Iberia, causing extensional stress regimes over high‐topography regions Both GPE and the long‐wavelength topography of Iberia result from the propagation of plate boundary stresses into the intraplate domain